ChemInform Abstract: Alkaloids of the South African Amaryllidaceae: A Review. Issue 30 (29th July 2014) - Nair, Jerald J.; Bastida, Jaume; Codina, Carles; Viladomat, Francesc; van Staden, Johannes
Abstract Review: 115 refs.